Deep ecomorphological and genetic divergence in Steller's Jays (Cyanocitta stelleri, Aves: Corvidae). Issue 12 (30th November 2022) - Cicero, Carla; Mason, Nicholas A.; Oong, Zheng; Title, Pascal O.; Morales, Melissa E.; Feldheim, Kevin A.; Koo, Michelle S.; Bowie, Rauri C. K.
Abstract: The relationship between ecology and morphology is a cornerstone of evolutionary biology, and quantifying variation across environments can shed light on processes that give rise to biodiversity. Three morphotypes of the Steller's Jay ( Cyanocitta stelleri ) occupy different ecoregions in western North America, which vary in climate and landcover. These morphotypes (Coastal, Interior, Rocky Mountain) differ in size, plumage coloration, and head pattern. We sampled 1080 Steller's Jays from 68 populations (plus 11 outgroups) to address three main questions using data on morphology, plumage, genetics (mtDNA, microsatellites), and ecological niches: (1) How do phenotypic and genetic traits vary within and among populations, morphotypes, and ecoregions? (2) How do population‐level differences in Steller's Jays compare with other sister species pairs of North American birds? (3) What can we infer about the population history of Steller's Jays in relation to past climates, paleoecology, and niche evolution? We found substantial morphological, genetic, and ecological differentiation among morphotypes. The greatest genetic divergence separated Coastal and Interior morphotypes from the Rocky Mountain morphotype, which was associated with warmer, drier, and more open habitats. Microsatellites revealed additional structure between Coastal and Interior groups. The deep mtDNA split between Coastal/Interior and Rocky Mountain lineages of Steller's Jay (ND2 7.8%) is older than most North American avian sister species and dates to approximately 4.3 mya. Interior and Rocky Mountain morphotypes contact across a narrow zone with steep clines in traits and reduced gene flow. The distribution of the three morphotypes coincides with divergent varieties of ponderosa pine and Douglas fir. Species distribution models support multiple glacial refugia for Steller's Jays. Our integrative dataset combined with extensive geographic sampling provides compelling evidence for recognizing at least two species of Steller's Jay. Abstract : Three morphotypes of the Steller's Jay ( Cyanocitta stelleri ) occupy different ecoregions in western North America, which vary in climate and landcover. We found substantial morphological, genetic, and ecological differentiation among morphotypes. Our integrative dataset combined with extensive geographic sampling provides compelling evidence for recognizing at least two species of Steller's Jay.